Hydro electricia / Nur Shazwani Amirah Zainal Ariffin … [et al.] - Zainal Ariffin, Nur Shazwani Amirah; Jamaludin, Maizurah; Mohd Faisal, Falisa Liyana; Mohammad Razin, Ridhwa Huda; Shabudin, Alwi (Research Innovation Business Unit, 2014)
Hydro Electricia Malaysia needs alternative energy sources of power supplies beyond 2020. Reliable energy plays an important role in achieving economics stability. Global industrialisation, technological, economic, and population growth result in the increase in demand for energy every day and every country is struggling to meet with this ever-growing demand for energy. Malaysia’s electricity demand is expected to increase in the future. Hydro Electricia is inspired by the concept of hydro-power plant which uses an electricity generator to extract energy from moving water. In the past people used rivers, lakes or damp to produce hydro-power plant but Hydro Electricia is an innovation where we used the concept of hydro-power in a box as an alternative to power supply. Hydro Electricia uses the gravity concept. We put the small water tank on the top of the box to release the water and make sure the water falls on the propellers. When the water falls, it will turn the propellers to generate power. The faster the propellers spin, the more power / electric will be generated. The water inside the box will be recycled. Water pump is used to push the water up into the small tank at the top and complete the circulation. Since the cost of living nowadays is increasing and the electricity tariff is high, Hydro Electricia offers an alternative. Hydro Electricia can be used as a measure to preserve the existing power supply for the future. The advantage of using the concept of hydro-power plant which is generated from water is that once generation facilities are built, it is easy to maintain and operate them. Electricity generated from water is clean and as it does not require any fossil fuels burning. The materials used in making the Hydro Electricia are not expensive and are affordable. Other than that, it is easy to make and safe. In conclusion, the Hydro Electricia can be very helpful in the future to meet the need for increased energy supply.